Information Technology Adoption and Knowledge Sharing Intention: The Mediating Role of Leadership Style - Widodo, Adi; Putra, Firdaus; Nadeak, Multi; Novitasari, Dewiana; Asbari, Masduki (International Journal of Social and Management Studies, 2022)
The purpose of this study is to investigate the effect of information technology adoption on knowledge sharing intention by involving the leadership style variable as a mediator. The sample of this research was taken from 102 lecturers of a private university in Indonesia using a simple random sampling technique and using SEM (Structural Equation Model) with SmartPLS version 3.0 software as a statistical tool. The results of this study indicate that information technology adoption has a positive and significant effect on knowledge sharing intention, either directly or through leadership style mediation. Therefore, leadership style can be a variable mediator that strengthens the influence of information technology adoption on knowledge sharing intention.